2019
DOI: 10.1159/000495407
|View full text |Cite
|
Sign up to set email alerts
|

Over Ten-Cell Good Embryo Transfers on Day Three have Equivalent Clinical Outcomes with Those of Eight-Cell Embryos in Female Patients Aged ≤35 Years: A Retrospective Cohort Study

Abstract: Background/Aim: To compare the clinical outcomes between > 10- and 8-cell good quality embryos on day 3. Methods: A retrospective study of a cohort of 459 patients was included in the fresh embryo transfer (ET) cycle group from January 2009 to April 2016. In this group, 2 good quality embryos on day 3, were transferred on corresponding dates, in 75 patients (> 10-cell embryos), and in 384 patients (8-cell embryos). Seven hundred and forty four patients, with 1 blastocyst transferred derived from > 10-cell (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Nonetheless, these results were contradicted with Moayeri et al [24] showing that cellular fragmentation, instead of cell number, acted as a sensitive proxy for predicting chromosomally normal embryos. In another retrospective study, Zhao et al [15] also found that > 10-cell derived blastocysts had similar aneuploidy rates to 8-cell derived blastocysts (55.6% vs. 55.9%). More recently, Pons et al [13] analyzed the PGT-A data of 4028 embryos in total and further confirmed that the ploidy of > 11-cell embryos was comparable with that of 8-cell embryos at the blastocyst stage (OR 1.20, 95% CI 0.92-1.56).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Nonetheless, these results were contradicted with Moayeri et al [24] showing that cellular fragmentation, instead of cell number, acted as a sensitive proxy for predicting chromosomally normal embryos. In another retrospective study, Zhao et al [15] also found that > 10-cell derived blastocysts had similar aneuploidy rates to 8-cell derived blastocysts (55.6% vs. 55.9%). More recently, Pons et al [13] analyzed the PGT-A data of 4028 embryos in total and further confirmed that the ploidy of > 11-cell embryos was comparable with that of 8-cell embryos at the blastocyst stage (OR 1.20, 95% CI 0.92-1.56).…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, only limited studies have been conducted to investigate the impact of increased day 3 cell number on clinical outcomes of cleavage-stage embryo transfer cycles [6,14,15]. Based on the national SART CORS database, Racowsky et al [6] found that there was a significant decline in LBR from embryos comprised of 8 cells to those with higher cell counts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations